2017
DOI: 10.1111/codi.13505
|View full text |Cite
|
Sign up to set email alerts
|

An unrestricted diet for uncomplicated diverticulitis is safe: results of a prospective diverticulitis diet study

Abstract: The incidence of complications among patients taking an unrestricted diet during an initial acute uncomplicated episode of diverticulitis was in line with that reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
1
18
0
3
Order By: Relevance
“…A retrospective study showed no increase in complications in a group of patients with a solid food diet compared to several types of dietary restrictions [96]. A prospective single-arm study with an unrestricted diet found an 8.1% complication rate after 6 months, which is comparable to rates in the literature on uncomplicated diverticulitis [97]. Additionally, a randomized trial found no increased pain scores, no increased length of hospital stay and no treatment failures in patients with an unrestricted oral regimen compared to an intravenous regimen including a minimum 24 h of fasting [98].…”
Section: Which Group Of Diverticulitis Patients Can Safely Be Treatedmentioning
confidence: 68%
“…A retrospective study showed no increase in complications in a group of patients with a solid food diet compared to several types of dietary restrictions [96]. A prospective single-arm study with an unrestricted diet found an 8.1% complication rate after 6 months, which is comparable to rates in the literature on uncomplicated diverticulitis [97]. Additionally, a randomized trial found no increased pain scores, no increased length of hospital stay and no treatment failures in patients with an unrestricted oral regimen compared to an intravenous regimen including a minimum 24 h of fasting [98].…”
Section: Which Group Of Diverticulitis Patients Can Safely Be Treatedmentioning
confidence: 68%
“…A prospective, uncontrolled study of an unrestricted diet in 86 patients with uncomplicated diverticulitis concluded that this was well-tolerated, although 8% had serious adverse events and 20% had ongoing symptoms. 123 A multicenter trial is underway to evaluate an unrestricted vs a progressive diet in uncomplicated diverticulitis. Most guidelines do not address pain control.…”
Section: Pharmacologic Agentsmentioning
confidence: 99%
“…Thus, any over‐ and under‐reporting of diverticular disease in the NPR will shift estimates in opposite directions. The study does not yield any information on the incidence of diverticular disease treated in an outpatient setting, or resolving without any contact with a healthcare facility. Incomplete coverage of the NPR before 1987 (approximately 60 per cent coverage in 1977 and 85 per cent in 1984) will have led to some recurrent cases being misclassified as incident, particularly at the start of the study.…”
Section: Discussionmentioning
confidence: 99%